Noise management to achieve superiority in quantum information systems. (6th August 2017) - Nemoto, Kae; Devitt, Simon; Munro, William J.
Abstract : Quantum information systems are expected to exhibit superiority compared with their classical counterparts. This superiority arises from the quantum coherences present in these quantum systems, which are obviously absent in classical ones. To exploit such quantum coherences, it is essential to control the phase information in the quantum state. The phase is analogue in nature, rather than binary. This makes quantum information technology fundamentally different from our classical digital information technology. In this paper, we analyse error sources and illustrate how these errors must be managed for the system to achieve the required fidelity and a quantum superiority. This article is part of the themed issue 'Quantum technology for the 21st century'.